PERANCANGAN KONSEP DAN LAYOUT APLIKASI BERBASIS WEBSITE E-CANTEEN UPN VETERAN JAWA TIMUR - I Desak Made Aprilia Anggraeni Pradanti; Widyasari Widyasari; Diana Aqidatun Nisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
The canteen is a place that we often encounter in various locations, one of which is in educational institutions such as campuses or universities. One of them is the East Java UPN Veterans canteen called